Aloe vera extract-assisted sol-gel synthesis of NiOx nanopyramids for supercapacitor application - Selvanathan V.; Islam M.A.; Kiong T.S.; Razali S.A.; Alharbi H.F.; Akhtaruzzaman M. (Elsevier Ltd, 2025)
Green synthesis of metal oxide nanoparticles is a cost-effective and sustainable approach that allows tailoring of the size and shape of the nanostructures for versatile applications. In this study, aloe vera extract-assisted sol-gel synthesis of nickel oxide nanoparticles (NiOx NPs) was explored for supercapacitor application. The NiOx NPs were synthesized at different aloe vera concentrations (2.5 and 5 wt%) and calcination temperatures (300, 400 and 500 C). The phytochemical-assisted synthesis yielded NiOx nanopyramids with pores on their surface which widens as calcination temperature increases. As confirmed by XRD analysis, NiOx crystallite size also increased at higher calcination temperatures. Upon electrochemical characterization, NiOx-400B which was synthesized with 5 wt% aloe vera extract at 400 C recorded the highest specific capacitance of 721 F g?1 at 1 A g-1 current density with the energy and power density of 10.38 Whkg?1 and 241.08 W kg-1 respectively. The charge storage mechanisms in the samples were gauged using Dunn's method which revealed that NiOx synthesized at higher calcination temperatures exhibited a greater contribution of the diffusion-controlled process. The optimized composition, NiOx-400B, also demonstrated excellent cycle stability by retaining up to 90.4 % of its original capacitance over 1500 cycles. This work is an attempt to investigate the viability of green synthesized nanoparticles in energy storage applications and the novel NiOx nanopyramid substantiates its prospect as a good electrode material for supercapacitors. ? 2024 Elsevier Ltd and Techna Group S.r.l.